The impact of players` motor skills on match performance in top German Bundesliga teams. - Konefal, M.; Chmura, P.; Kowalczuk, E.; Andrzejewski, M.; Chmura, J. (Trends in Sport Sciences, 2015)
Introduction. Soccer is a highly dynamic and acyclical game and a soccer player`s performance during a match involves a high variability of actions since. Aim of Study. The aim of the present study was to determine the effects of endurance and speed skills of players from two top German Bundesliga teams on their teams` final standings in the league table. Material and Methods. The study covered all 34 matches of the 2013/2014 season, and it consisted of 480 observations of 41 players. It was carried out using the Impire AG motion analysis system on the basis of official Deutscher Fußball-Bund (DFB) match reports. The players` endurance skills were estimated on the basis of total distance covered during match play and distances in different intensity ranges. The players` speed skills were assessed on the basis of the total number of performed sprints, sprinting distance, and maximal and mean running speed. Results. The results showed that the team which was ranked lower in the final league table scored higher in all players` motor parameters than the team which was ranked higher. Conclusions. Pre-season motor preparation of top German Bundesliga teams is not the decisive determinant of the teams` final standings in the league, and even the highest level of players` skills does not guarantee reaching the championship position.